Compressor Air Pressure and Brake Shield Distance Brake to Braking Accuracy on Brakes Antilock Braking System - Listiyono, Listiyono; Nurhadi, Nurhadi; Khambali, Khambali (CV. Creative Tugu Pena, 2022)
The development of automotive technology to date is very fast. In the city, it is almost rare to find conventional cars. Most are already using modern technology. The hallmark of modern cars is that they are not fully mechanical. Already combined with several electric and pneumatic tools. Until now the development in the field of chassis is endless. Its initial development began with the discovery of ABS (Anti Lock Brake System) brakes. Basically, ABS is followed by supporting components such as EBD, ESP, and so on.All of this is actually inseparable from the main function of braking. Namely so that the car can run well,, deceleration and stop as desired appropriately. The parts of the brakes that are most influential are the brake shoes and discs and the compressed air from the brakes. Also the most influential accuracy is the distance of the brake shroud. Therefore, in this study the aims of 1. To find the effect of pressure and brake shroud distance. 2. What is the minimum air pressure and brake shroud for the brakes to work properly (grip). This research uses experimental design method. The data is processed with the Minitab program. Data processing shows that: 1. The braking speed is influenced by the amount of compressed air pressure. Partially the distance of the brake shroud does not affect the braking speed. But the interaction of pressure and shroud distance has an effect on braking speed. 2. Air pressure that can be used as a fast ABS braking process is 3.75 – 4.25 (bar) with a shroud distance of 5 (mm). Keywords: Compressor Air Pressure, Braking Accuracy, Antilock Braking System